Population Structure of Siit Rattan (Daemonorops melanochaetes, Blume.) in The Coastal Forest of Tabanio Village, Takisung District, South Kalimantan - Fajeriadi, Hery; Dharmono, Dharmono (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2019)
Indonesia as the largest archipelago country in the world has a vast coastline. Various types of ecosystems are scattered on the coast, one of which is coastal forest. One of the functions of coastal forests is as a habitat for flora, including rattan siit (Daemonorops melanochaetes Blume). Siit rattan has a fairly stable commercial value on the market. Its strong structure makes it attractive, not only nationally, even internationally. This study aims to determine the population structure of siit rattan in the coastal forest of Tabanio Village, Takisung District, Tanah Laut Regency. Data collection was done with total roaming techniques, namely along the coastal forest with a width of 50 m and a length of one thousand m to the south. The results of the study were analyzed descriptively. The age of siit rattan (Daemonorops melanochaetes Blume) includes a wide base pyramid, without any stopping or decaying of growth in the pre-reproductive and reproductive phases. Natality rattan siit went well and almost did not experience mortality because the coastal forest of Tabanio Village was guarded by custom by the local community. Environmental factors that inhibit the reproductive rate of siit rattan are air temperatures that were too high from the optimal temperature of siit rattan breeding.